Modern literary theory : a reader - Rice, Philip; Waugh, Patricia (London : Arnold ; New York : Bloomsbury Academic, 2011)
This book provides an introduction to theoretical writing over the past 25 years, giving examples of the writings of many key figures in the field together with seminal essays that have explored and extended the implications of critical theory.
Includes bibliographical references (p. [484]-489) and index.
Keywords: Literature -- History and criticism -- Theory, etc